Impact of High Age and Comorbidity on Management Decisions and Adherence to Guidelines in Patients with Keratinocyte Skin Cancer - Satish F.K. Lubeek; Celia A.J. Michielsens; Rinke J. Borgonjen; Ewald M. Bronkhorst; Peter C.M. Kerkhof; Marie-Jeanne P. Gerritsen (Medical Journals Sweden, 2017)
Appropriate medical decision-making in patients with keratinocyte skin cancer (KSC) can be challenging, especially in those with a limited life expectancy (LEx). Treatment should be beneficial for the individual patient, the risk of both over- and under-treatment should be carefully considered, and deviation from guideline recommendations may be necessary. In this study retrospective analysis was performed to determine the influence of age and comorbidity, both factors strongly related to limited LEx, on KSC management in daily practice. After analysis of 401 patients it was found that management in patients with KSC is not influenced, or is only minimally influenced, by high age and comorbidity. Better integration of aspects related to a limited LEx in KSC management might optimize care and prevent overtreatment. Future research on the general prognostication, prediction of the patient burden caused by tumour and treatment, and time-to-benefit in KSC management is strongly recommended.